Frogs of populated localities at west coast and Kudat divisions, Sabah, Malaysia: assemblage of merely commensal species or not? - Boon, Hee Kueh (Penerbit Universiti Malaysia Sabah, 2006)
Inventory-based studies on frogs in Sabah have focused on protected areas.